Perovskite type high-temperature-resistant CO2 methanation catalyst as well as preparation and application thereof
Through the preparation method of perovskite catalyst, combined with density functional theory and solvent combustion method, the problem of catalyst inactivation at high temperature is solved, high activity and low energy consumption of low-temperature CO2 methanation reaction are achieved, and the stability of the catalyst is improved and anti-sintering properties.
Patent Information
- Application Number
- CN202411467805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-07
AI Technical Summary
The existing carbon dioxide methanation catalysts are prone to deactivate under high temperature conditions, and the nickel-based catalysts have insufficient thermal sintering and thermal conductivity, which makes the reaction temperature difficult to control. The precious metal catalysts are restricted by industrial applications due to their high prices.
The preparation method of perovskite catalyst was adopted to optimize the catalyst surface structure through density functional theory. Combined with experimental verification, the combination of CaZrO3 and NiO on the ZrO2 carrier was used to increase the loading rate of active components by multiple impregnation and solvent combustion. and dispersion, reduce the high-temperature calcination time, form nano-scale NiO particles and CaZrO3 uniformly dispersed, and improve the reactivity and stability of the catalyst.
Improve the CO2 methanation reaction activity under low temperature conditions, reduce energy consumption, enhance the anti-sintering and carbon deposit properties of the catalyst, improve the high-temperature stability and reaction activity of the catalyst, and reduce process costs.
Smart Images

Figure CN119259056A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dioxide methanation catalysts, and more specifically, relates to a preparation method of a perovskite-type high-temperature resistant CO2 methanation catalyst and the prepared catalyst. In addition, the present invention also relates to the application of the catalyst in the field of CO2 methanation. Background Art
[0002] In recent years, universities and research institutes around the world have conducted a lot of research on "Carbon Capture and Utilization (CCUS)". Among them, CO2 hydrogenation to produce methane (hereinafter referred to as CO2 methanation) is a recently developed chemical energy storage technology.
[0003] At present, the catalysts and preparation methods reported for carbon dioxide methanation are basically nickel-based catalysts for syngas conversion. For example, Chinese patent CN 104475119 B provides a CO2 high-temperature methanation catalyst, especially a high-concentration CO2 methanation catalyst, which includes a carrier, an active component and an auxiliary agent; the active component is nickel oxide, and the auxiliary agent is aluminum oxide, lanthanum oxide and chromium oxide; the weight parts of each component are: 20-40 parts of carrier, 40-60 parts of nickel oxide, 15-25 parts of aluminum oxide, 2-4 parts of lanthanum oxide, and 1-3 parts of chromium oxide. The CO2 high-temperature methanation catalyst provided by this invention is mainly suitable for the methanation reaction of gas components with high CO2 content in coal-to-syngas. For example, Chinese patent CN 116899572 A discloses a preparation method and application of a high-temperature resistant CO2 methanation catalyst, the preparation method is: grind coal powder, potassium salt, nickel salt, magnesium salt and aluminum salt uniformly to obtain a uniform mixture; roast the mixture at 600-900°C for 2-8 hours in a flowing inert atmosphere; after the roasting, keep the mixture in a flowing inert atmosphere to cool to room temperature, transfer it to a water bath for reflux treatment, obtain a solid powder sample, filter and wash the solid powder sample until the pH value of the supernatant is neutral, then wash it with ethanol, filter and dry it to obtain a catalyst precursor; knead the catalyst precursor, granulate it, and steam cure it to obtain a high-temperature resistant methanation catalyst. The high-temperature resistant carbon dioxide methanation catalyst provided by this invention method is also mainly applicable to the field of methanation catalysis of coal-to-synthetic natural gas.
[0004] The biggest problem with nickel-based catalysts is that they are easily deactivated by the formation of nickel carbonyl. At the same time, CO2 methanation is a highly exothermic reaction, which requires very high heat resistance and thermal conductivity of the catalyst carrier. Existing Ni-based catalysts are usually based on alumina and silica. The reaction temperature is difficult to control during the reaction, which can easily cause thermal sintering of active metals and the active metals easily react with alumina and silica carriers at high temperatures to form spinel phases and lose catalytic activity.
[0005] There are also some reports of carbon dioxide methanation catalysts at home and abroad, which are catalysts with Ru, Pt, Pd, Rh and other precious metals as active components. Among them, Ru, Rh and other precious metal catalysts have excellent performance and good resistance to carbon deposition, but their high prices limit their industrial applications. In fact, Ni-based catalysts have relatively high activity and selectivity and are inexpensive and easy to obtain. If the technical problems in their application process can be overcome, the potential for industrial application is even broader.
[0006] Chinese patent CN 109261183 A discloses a cobalt-based catalyst for carbon dioxide methanation, which is composed of cobalt tetraoxide, cobalt carbide and modified titanium carbide, and its weight composition is cobalt tetraoxide: cobalt carbide: modified titanium carbide = (0.4-0.8): (0.2-0.4): 1, and is prepared by equal volume impregnation. However, although the cobalt-based catalyst exhibits high reaction activity and chain growth ability, as well as good mechanical strength and stability in the CO2 hydrogenation reaction, due to the inherent chemical inertness of CO2 itself, the methanation reaction process needs to be carried out under high temperature and high pressure conditions of reaction temperature 300-400°C and reaction pressure 2.0-5.0 MPa, resulting in high energy consumption in the entire process.
[0007] Chinese patent CN 109999814 A discloses a nano-metal nickel catalyst for carbon dioxide methanation reaction and a preparation method. The method is to weigh nickel ions, magnesium ions, citric acid and ethylene glycol according to a certain molar ratio and dissolve them in deionized water to prepare a mixed solution, impregnate the mixed solution into a ZrO2 carrier, and then complex, dry and calcine to obtain a catalyst precursor with ZrO2 as the carrier; load the precursor into a fixed bed reactor and perform reduction treatment; ZrO2 is converted into a single crystal monoclinic phase ZrO2. The disadvantage of the invention method is that the active component loading rate is low, and it is easy to agglomerate during the high-temperature calcination process, resulting in poor method reproducibility. Summary of the invention
[0009] In order to solve the technical problems existing in the prior art, the inventors conducted a systematic and in-depth study on the problem of CO2 methanation, and comprehensively analyzed the advantages and disadvantages of various existing CO2 methanation catalysts. On this basis, the present invention firstly used the density functional theory (DFT) research method to theoretically calculate the ideal catalyst surface structure parameters, and then combined with the experimental research results to verify and correct them, thereby developing a new type of CO2 methanation catalyst. The catalyst applied to the CO2 methanation reaction can improve the reaction activity of CO2 methanation while reducing the reaction activation energy, thus providing a new idea for the CO2 methanation reaction under low temperature conditions.
[0010] In order to achieve the above object, the present invention adopts the following technical solution.
[0011] A method for preparing a perovskite-type high temperature resistant CO2 methanation catalyst comprises the following steps: 1) The calcium source and monoclinic ZrO2 are mixed in a molar ratio of 1:1, and then the mixture is placed in a ball mill, with anhydrous ethanol as the ball milling medium, and after ball milling for 5 to 8 hours, it is placed in a high temperature environment of not less than 1600°C and calcined for 2 to 5 hours, cooled to room temperature, and the sample is taken out, crushed, ball milled, and sieved to obtain CaZrO3 powder; 2) CaZrO3 powder, nickel source, soluble organic fuel and a certain amount of ethylene glycol in a molar ratio of 1:0.2~0.8:0.1~0.5 are dissolved in deionized water and stirred to obtain a dispersion. The carrier monoclinic ZrO2 powder is then placed in the dispersion and subjected to ultrasonic treatment for 5~12 h. After the treatment, the resulting mixture is heated at 300~550°C until spontaneous combustion occurs. After the flame is extinguished, the mixture is calcined at 800~900°C for 1~2 h. The calcined product is collected, crushed, sieved, kneaded and granulated to obtain a NiO-CaZrO3 / ZrO2 catalyst with a certain mesh size.
[0012] Preferably, the calcium source is a mixture of one or more of calcium carbonate, calcium hydroxide or calcium oxide.
[0013] Preferably, the nickel source is a mixture of one or more of nickel nitrate, nickel acetate and nickel carbonate.
[0014] Preferably, the soluble organic fuel is any one of oxalic acid, tartaric acid, glycine or mannitol.
[0015] Preferably, the ball milling rate is 125-225 r / min, and the time is 5-8 h.
[0016] The perovskite-type high-temperature resistant CO2 methanation catalyst prepared by the above-mentioned preparation method has a composition of AB / ZrO2; wherein: component A is NiO, with a content of 9-18%; component B is CaZrO3, with a content of 12-25%; the balance is carrier ZrO2; the particle size of the NiO-CaZrO3 / ZrO2 catalyst is 50-250 mesh, and the specific surface area is 150-200 m 2 / g, pore size 12~18nm.
[0017] The present invention also relates to the use of the above-mentioned perovskite-type high temperature resistant CO2 methanation catalyst in a fixed bed reactor. Before application, the catalyst is first placed in a fixed bed reaction, and then treated in situ with a H2 / N2 mixed gas at 550°C for 2 to 8 h to obtain a reducing Ni-CaZrO3 / ZrO2 catalyst, and then the temperature is adjusted to 200 to 380°C, the reaction pressure is 0.1 to 3MPa, and then a H2 and CO2 mixed gas with H2 / CO2=4 is introduced at a gas space velocity of 5000 to 12000 mL / (g·h) for reaction.
[0018] Furthermore, during the above-mentioned in-situ treatment of the catalyst, the composition of the H2 / N2 mixed gas is 5-85% (V / V%) H2 and 15-95% (V / V%) N2, the reduction temperature is 200-380°C, the pressure is 0.1-1.5 MPa, and the reducing gas space velocity is 5000-8000 mL / (g·h).
[0019] Compared with the prior art, the preparation method of the catalyst of the present invention has the following advantages and significant technical progress: (1) In the preparation method of the catalyst of the present invention, the active component adopts a multiple impregnation method to improve the loading rate of the active component. At the same time, by adding a soluble organic fuel to the raw material, the soluble organic fuel reaches the ignition point and spontaneously ignites during the heating and evaporation concentration process at 300-550°C. The large amount of gas generated during the combustion process, on the one hand, produces a rich pore structure inside the catalyst precursor, increases the specific surface area of the catalyst, and provides more active sites for the dispersion of the active component. On the other hand, the large amount of gas generated during the combustion process makes the active metal element Ni reach a nanometer-level distribution, which helps to improve the dispersibility of the active component and greatly improves the utilization rate of the active component. In addition, in the preparation method of the catalyst of the present invention, since the solvent combustion method is used to treat the catalyst intermediate, the high-temperature roasting treatment time is greatly reduced, thereby reducing the preparation time and energy consumption of the catalyst.
[0020] (2) In the preparation method of the catalyst of the present invention, a perovskite-type high entropy oxide CaZrO3 component is introduced into the catalyst structure. After being applied to the CO2 reaction process, since the surface of CaZrO3 can adsorb a large amount of CO2 molecules, micro-reaction gas enrichment zones are formed around the Ni active component, thereby allowing CO2 and H2 to react rapidly to generate CH4 molecules. Therefore, compared with the existing catalysts, after the catalyst of the present invention is applied, the active components and Ni and CaZrO3 produce a synergistic effect, thereby improving the reaction activity of the catalyst.
[0021] (3) The preparation method of the catalyst of the present invention comprises adding an appropriate amount of ethylene glycol to the raw materials, and then undergoing a solvent combustion process, so that the NIO nanoparticles and the CaZrO3 perovskite phase components can be uniformly dispersed on the ZrO2 surface, wherein the CaZrO3 perovskite phase components simultaneously generate certain intermolecular forces on the NiO molecules and the ZrO2 molecules. By selecting a suitable molar ratio of the NiO component to the CaZrO3 component, the problem that the NiO component is easily lost during the application process due to the weak interaction between NiO and ZrO2, resulting in the catalyst activity decreasing too quickly, can be effectively improved, and the catalyst's anti-sintering ability is also improved. The prepared catalyst has good high-temperature stability, strong resistance to carbon deposition and anti-sintering performance, and effectively reduces the phenomenon of catalyst surface carbon inactivation caused by "heat runaway" due to the CO2 methanation reaction being an exothermic reaction, or catalyst inactivation caused by high-temperature agglomeration of metal Ni. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD patterns of the catalysts prepared in Examples 2 to 5 of the present invention; Figure 2 TEM images of the catalysts prepared in Examples 1 ((a) in the figure) and 2 ((b) in the figure) of the present invention; Figure 3 The catalytic performance of the catalysts prepared in Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] [Example 1] 1. Preparation of catalyst (1) Mix 8 g of CaCO3 and 10 g of monoclinic ZrO2 evenly, then place the mixture in a ball mill with an appropriate amount of anhydrous ethanol as the ball milling medium. After ball milling for 5 h, place the mixture in a high temperature environment of not less than 1600 °C and calcine for 8 h. Cool, crush, ball mill, and sieve to obtain CaZrO3 powder.
[0025] (2) Take 7.2 g CaZrO3 and 3.8 g nickel acetate, 1.8 g tartaric acid and 10 ml ethylene glycol and dissolve them in deionized water to obtain a mixed solution. Then, place 11.6 g monoclinic ZrO2 powder in the dispersion and treat it with ultrasound for 5-12 h. After the treatment, heat the mixture at 300-550 °C until it spontaneously ignites. After the flame is extinguished, calcinate it at 800-900 °C for 1-2 h. Collect the calcined products, ball-mill and granulate them to obtain NiO-CaZrO3 / ZrO2 catalyst with a particle size of 50-250 mesh, which is marked as NCZ (6% Ni).
[0026] 2. Catalyst characterization The SBET, average pore size and total pore volume (VT) of the catalyst were quantitatively analyzed using the Brunauer-Emmett-Teller (BET) technique on a Quanta Chromium Quadra-Sorb SI device. The particle size of the NiO-CaZrO3 / ZrO2 catalyst prepared by the method of the present invention is 50-250 mesh and the specific surface area is 150-200 m 2 / g, pore size 12~18nm.
[0027] X-ray diffraction (XRD) analysis was performed using a Bruker D-MAX 2500 X-ray powder diffractometer, which used Cu-Kα radiation at a scanning rate of 8° / min to reveal the crystal structure of the catalyst. Since the Ni content in this example is close to that in Example 2, the XRD of the catalyst is also close, so it is not listed in Figure 1. Figure 1 It can be seen that the present invention successfully prepared the NiO-CaZrO3 / ZrO2 catalyst.
[0028] The microstructure of the reduced NCZ (6% Ni) catalyst was analyzed using TEM images. Figure 2 As shown in (a), the TEM image of the NCZ (6% Ni) catalyst shows Ni particles on the (010) plane with a lattice spacing of 2.30 Å. Around these Ni NPs, the lattice spacings of 4.0 Å, 3.5 Å, and 2.84 Å correspond to the crystal planes (020), (121), and (100) of PTO-CaZrO3, respectively, further confirming the test results of XRD.
[0029] (III) Catalytic performance test The evaluation of CO2 methanation reaction was carried out in a micro fixed bed reactor. Before the reaction, the catalyst needs to be activated in situ. The activation atmosphere uses a H2 / N2 mixed gas, which consists of 5-85% (V / V%) H2 and 15-95% (V / V%) N2. During the activation process, the temperature is 200-380°C, the pressure is 0.1-1.5 MPa, and the gas space velocity is 5000-8000 mL / (g·h). The specific steps of the catalyst performance test are as follows: the catalyst (200 mg) is treated with H2 in situ at 550°C for 2 hours. Then, the temperature in the reactor is adjusted to 200-380 °C and the reaction pressure is 0.1-3MPa, and then a H2 and CO2 mixed gas with H2 / CO2=4 is introduced at a gas space velocity of 5000-12000 mL / (g·h) for reaction. The reaction process was analyzed by FULIGC9790II gas chromatograph equipped with TCD detector, using N2 as internal standard gas as carrier gas, and keeping the molar ratio of H2 / CO2 / N2 at 16:4:5. In addition, in order to evaluate the stability of the catalyst, a stability test was carried out at 550°C for 100 hours. Activity tests in the temperature range of 200 to 550°C were carried out before and after the stability test to facilitate comparative analysis.
[0030] The results of catalyst activity and performance evaluation are shown in Figure 3 .
[0031] [Example 2] (1) Mix 6 g of CaCO3, 2 g of CaO and 10 g of monoclinic ZrO2 evenly, then place the mixture in a ball mill with an appropriate amount of anhydrous ethanol as the ball milling medium. After ball milling for 5 h, place the mixture in a high temperature environment of not less than 1600 °C and calcine for 7 h. Cool, crush, ball mill and sieve to obtain CaZrO3 powder.
[0032] (2) Weigh 7.2 g of CaZrO3 powder, dissolve it with 4.3 g of nickel acetate, 2.2 g of tartaric acid and 10 ml of ethylene glycol in deionized water to obtain a mixed solution, then place 11 g of monoclinic ZrO2 powder in the dispersion and treat it with ultrasound for 5-12 h. After the treatment, place the resulting mixture in a muffle furnace at 300-550 °C and heat it until it spontaneously ignites. After the flame is extinguished, calcinate it at 800-900 °C for 1-2 h. Collect the calcined products, ball mill and granulate them to obtain NiO-CaZrO3 / ZrO2 catalyst with a particle size of 50-250 mesh, which is marked as NCZ (9% Ni).
[0033] The characterization and performance test of NCZ (9% Ni) catalyst refer to Example 1. The average particle size of NCZ (9% Ni) catalyst prepared in Example 2 is 50-250 mesh, and the average specific surface area is 150-200 m 2 / g, average pore size 12~18nm. XRD spectrum see Figure 1 ,from Figure 1 It can be seen that the present invention successfully prepared NiO-CaZrO3 / ZrO2 catalyst. The catalyst activity and performance evaluation results are shown in Figure 3 .
[0034] [Example 3] (1) Mix 6.5 g of Ca(OH)2 and 10 g of monoclinic ZrO2 evenly, then place the mixture in a ball mill with an appropriate amount of anhydrous ethanol as the ball milling medium. After ball milling for 3 h, place the mixture in a high temperature environment of not less than 1600 °C and calcine for 6 h. Cool, crush, ball mill, and sieve to obtain CaZrO3 powder.
[0035] (2) Weigh 7.2 g of CaZrO3 powder, dissolve it with 4.4 g of nickel nitrate, 1.6 g of oxalic acid and 10 ml of ethylene glycol in deionized water to obtain a mixed solution, then place 6 g of monoclinic ZrO2 powder in the dispersion and treat it with ultrasound for 5-12 h. After the treatment, place the resulting mixture in a muffle furnace at 300-550 °C and heat it until it spontaneously ignites. After the flame is extinguished, calcinate it at 800-900 °C for 1-2 h. Collect the calcined products, ball mill and granulate them to obtain NiO-CaZrO3 / ZrO2 catalyst with a particle size of 50-250 mesh, which is marked as NCZ (9% Ni).
[0036] The characterization and performance test of NCZ (12% Ni) catalyst are shown in Example 1. Since the structural and performance parameters of the catalyst are basically the same as those of Examples 1 and 2, they are not listed here. Figure 1 ,from Figure 1 It can be seen that the present invention successfully prepared NiO-CaZrO3 / ZrO2 catalyst. The catalyst activity and performance evaluation results are shown in Figure 3 .
[0037] [Example 4] (1) Mix 4.5 g Ca(OH)2, 2 g CaO and 10 g monoclinic ZrO2 evenly. Then place the mixture in a ball mill with an appropriate amount of anhydrous ethanol as the ball milling medium. After ball milling for 2 h, calcine at a high temperature of not less than 1600 °C for 6 h. Cool, crush, ball mill and sieve to obtain CaZrO3 powder.
[0038] (2) Weigh 7.2 g of CaZrO3 powder, dissolve it with 3.5 g of nickel carbonate, 1.4 g of glycine and 10 ml of ethylene glycol in deionized water to obtain a mixed solution, then place 4.7 g of monoclinic ZrO2 powder in the dispersion and treat it with ultrasound for 5-12 h. After the treatment, place the resulting mixture in a muffle furnace at 300-550 °C and heat it until it spontaneously ignites. After the flame is extinguished, calcinate it at 800-900 °C for 1-2 h. Collect the calcined products, ball mill and granulate them to obtain NiO-CaZrO3 / ZrO2 catalyst with a particle size of 50-250 mesh, which is marked as NCZ (15% Ni).
[0039] The characterization and performance test of NCZ (15% Ni) catalyst are shown in Example 1. Since the structural and performance parameters of the catalyst are basically the same as those of Examples 1 and 2, they are not listed here. Figure 1 ,from Figure 1 It can be seen that the present invention successfully prepared NiO-CaZrO3 / ZrO2 catalyst. The catalyst activity and performance evaluation results are shown in Figure 3 .
[0040] [Example 5] (1) Mix 6 g of CaO and 10 g of monoclinic ZrO2 evenly, then place the mixture in a ball mill with an appropriate amount of anhydrous ethanol as the ball milling medium. After ball milling for 2 h, place the mixture in a high temperature environment of not less than 1600 °C and calcine for 5 h. Cool, crush, ball mill, and sieve to obtain CaZrO3 powder.
[0041] (2) Weigh 7.2 g of CaZrO3 powder, dissolve it with 5.7 g of nickel nitrate, 3.7 g of mannitol and 10 ml of ethylene glycol in deionized water to obtain a mixed solution, then place 3.8 g of monoclinic ZrO2 powder in the dispersion and treat it with ultrasound for 5-12 h. After the treatment, place the resulting mixture in a muffle furnace at 300-550 °C and heat it until it spontaneously ignites. After the flame is extinguished, calcinate it at 800-900 °C for 1-2 h. Collect the calcined products, ball mill and granulate them to obtain NiO-CaZrO3 / ZrO2 catalyst with a particle size of 50-250 mesh, which is marked as NCZ (18% Ni).
[0042] The characterization and performance test of NCZ (18% Ni) catalyst are shown in Example 1. Since the structural and performance parameters of the catalyst are basically the same as those of Examples 1 and 2, they are not listed here. Figure 1 ,from Figure 1 It can be seen that the present invention successfully prepared NiO-CaZrO3 / ZrO2 catalyst. The catalyst activity and performance evaluation results are shown in Figure 3 .
[0043] Depend on Figure 3 It can be seen that the preparation method of the catalyst of the present invention can uniformly load highly dispersed nickel nanoparticles and perovskite-phase CaZrO3 on ZrO2, so the prepared series of NCZ catalysts show very good catalytic performance for CO2 methanation, high activity, excellent selectivity for CH4 and extremely high stability. In addition, the stability and anti-sintering performance of the NCZ catalyst are excellent, which is due to the effective interaction between CaZrO3 and Ni / ZrO2, which can not only prevent the agglomeration of the active component Ni, but also significantly improve the stability of the catalyst by improving the metal-support interaction and the high dispersibility of Ni / ZrO2, and improve the anti-sintering ability of the catalyst.
[0044] Although the above description has shown some of the best embodiments of the present invention, it is understandable to those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and any equivalent schemes made under the guidance of the principles and spirit of the present invention are limited by the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite-type high temperature resistant CO2 methanation catalyst, comprising the following steps: 1) The calcium source and the monoclinic ZrO2 powder are mixed in a material ratio of 1:1, and then the mixed material is placed in a ball mill, anhydrous ethanol is used as the ball milling medium, and after ball milling for a period of time, it is placed in a high temperature environment of not less than 1600°C for calcination for 2-5 hours, cooled, crushed, and sieved to obtain CaZrO3 powder; 2) CaZrO3 powder, nickel source, soluble organic fuel and a certain amount of ethylene glycol in a molar ratio of 1:0.2~0.8:0.1~0.5 are dissolved in deionized water and stirred to obtain a dispersion. The carrier monoclinic ZrO2 powder is then placed in the dispersion and subjected to ultrasonic treatment for 5~12 h. After the treatment, the resulting mixture is heated at 300~550°C until spontaneous combustion occurs. After the flame is extinguished, the mixture is calcined at 800~900°C for 1~2 h. The calcined product is collected, crushed, sieved, kneaded and granulated to obtain a NiO-CaZrO3 / ZrO2 catalyst with a certain mesh size.
2. The method for preparing the perovskite-type high temperature resistant CO2 methanation catalyst according to claim 1, characterized in that: The calcium source is a mixture of one or more of calcium carbonate, calcium hydroxide or calcium oxide.
3. The method for preparing the perovskite-type high temperature resistant CO2 methanation catalyst according to claim 1, characterized in that: The nickel source is a mixture of one or more of nickel nitrate, nickel acetate and nickel carbonate.
4. The method for preparing the perovskite-type high temperature resistant CO2 methanation catalyst according to claim 1, characterized in that: The soluble organic fuel is any one of oxalic acid, tartaric acid, glycine or mannitol.
5. The method for preparing the perovskite-type high temperature resistant CO2 methanation catalyst according to claim 1, characterized in that: The ball milling speed is 125-225 r / min, and the time is 5-8 h.
6. A perovskite-type high temperature resistant CO2 methanation catalyst prepared by the method for preparing a perovskite-type high temperature resistant CO2 methanation catalyst according to any one of claims 1 to 4, characterized in that: The composition of the catalyst is AB / ZrO2; wherein: component A is NiO, with a content of 9-18%; component B is CaZrO3, with a content of 12-25%; the balance is carrier ZrO2; the particle size of the NiO-CaZrO3 / ZrO2 catalyst is 50-250 mesh, and the specific surface area is 150-200 m 2 / g, pore size 12~18nm.
7. The perovskite-type high temperature resistant CO2 methanation catalyst according to claim 6 is used in a CO2 methanation reaction in a fixed bed reactor.
8. The perovskite-type high temperature resistant CO2 methanation catalyst according to claim 7 is applied to a CO2 methanation reaction in a fixed bed reactor, characterized in that: Before the reaction, the catalyst is first placed in a reactor, and is subjected to in-situ reduction treatment with a H2 / N2 mixed gas at 550°C for 2-8 h to obtain a Ni-CaZrO3 / ZrO2 catalyst, and then the temperature is adjusted to 200-380°C, the reaction pressure is 0.1-3MPa, and then a H2 and CO2 mixed gas with H2 / CO2=4 is introduced at a gas space velocity of 5000-12000 mL / (g·h) to react.
9. The perovskite-type high temperature resistant CO2 methanation catalyst according to claim 8 is used for CO2 methanation reaction in a fixed bed reactor, characterized in that: The H2 / N2 mixed gas comprises 5-85% (V / V%) H2 and 15-95% (V / V%) N2.
10. The perovskite-type high temperature resistant CO2 methanation catalyst according to claim 8 is used for CO2 methanation reaction in a fixed bed reactor, characterized in that: During the in-situ reduction treatment, the reduction temperature is 200-380°C, the pressure is 0.1-1.5 MPa, and the reducing gas space velocity is 5000-8000 mL / (g·h).
Citation Information
Patent Citations
A CO2 high-temperature methanation catalyst and its preparation and application methods
CN104475119B
Cobalt-based catalyst for carbon dioxide methanation, preparation method and application
CN109261183A
Nano metal nickel catalyst for CO2 methanation reaction and preparation method
CN109999814A
Preparation method and application of high-temperature-resistant CO2 methanation catalyst
CN116899572A
Cited By
Difunctional composite material as well as preparation method and application thereof
CN120437945A
Bifunctional composites, methods of making and using the same
CN120437945B
MgO-SiO2 composite oxide loaded La1-xCaxNiO3 catalyst as well as preparation method and application thereof
CN122538147A